Arrhythmic profile and 24-hour QT interval variability in COVID-19 patients treated with hydroxychloroquine and azithromycin. (1st October 2020) - Cipriani, Alberto; Zorzi, Alessandro; Ceccato, Davide; Capone, Federico; Parolin, Matteo; Donato, Filippo; Fioretto, Paola; Pesavento, Raffaele; Previato, Lorenzo; Maffei, Pietro; Saller, Alois; Avogaro, Angelo; et al.
Abstract: Background: Hydroxychloroquine and azithromycin combination therapy is often prescribed for coronavirus disease 2019 (COVID-19). Electrocardiographic (ECG) monitoring is warranted because both medications cause corrected QT-interval (QTc) prolongation. Whether QTc duration significantly varies during the day, potentially requiring multiple ECGs, remains to be established. Methods: We performed 12‑lead ECGs and 12‑lead 24-h Holter ECG monitoring in all patients aged <80 years admitted to our medical unit for COVID-19, in oral therapy with hydroxychloroquine (200 mg, twice daily) and azithromycin (500 mg, once daily) for at least 3 days. A group of healthy individuals matched for age and sex served as control. Results: Out of 126 patients, 22 (median age 64, 82% men) met the inclusion criteria. ECG after therapy showed longer QTc-interval than before therapy (450 vs 426 ms, p = .02). Four patients had a QTc ≥ 480 ms: they showed higher values of aspartate aminotransferase (52 vs 30 U/L, p = .03) and alanine aminotransferase (108 vs 33 U/L, p < .01) compared with those with QTc < 480 ms. At 24-h Holter ECG monitoring, 1 COVID-19 patient and no control had ≥1 run of non-sustained ventricular tachycardia ( p = .4). No patients showed "R on T" premature ventricular beats. Analysis of 24-h QTc dynamics revealed that COVID-19 patients had higher QTc values than controls, with no significant hourly variability. Conclusion: Therapy with hydroxychloroquine and azithromycin prolongs QTc interval in patients with COVID-19, particularly in those with high levels of transaminases. Because QTc duration remains stable during the 24 h, multiple daily ECG are not recommendable. Highlights: Combination therapy with hydroxychloroquine and azithromycin prolong QT-interval in patients with COVID-19 The risk of QTc-prolongation is higher in COVID-19 patients with high levels of transaminase. QTc values show temporal stability over the 24-h, with no differences among different times of the day. A periodic, not daily, QTc surveillance in COVID-19 patients is recommendable.